تحديد تركيز المعادن الثقيلة في بعض أنواع البهارات والأعشاب الطبية المحلية - عليا, تميم; سلامة, لينا (Latakia University Journal -Biological Sciences Series, 2019)
قدرت كمية العناصر الثقيلة الرصاص والكادميوم والكوبالت في بعض الأعشاب الطبية والبهارات الشائعة الاستعمال والمنتشرة في الأسواق المحلية السورية باستخدم جهاز الامتصاص الذري. بينت الدراسة وجود فروق في تراكيز المعادن المختلفة تبعاً للجزء المستعمل من النبات (جذر، ساق، الأوراق، ثمار .(تراوح تركيز العناصر الثقيلة من تراكيز صغيرة دون حد الكشف (Pb:0.0029, Cd:0.0002, Co:0.0028 mg/kg) إلى تراكيز عالية وصلت للرصاص إلى37mg/kg على أساس الوزن الجاف, بينما وصل الحد الأعظمي لتركيز الكادميوم في العينات المدروسة إلى 3.2mg/kg وللكوبالت 2.4mg/kg. كانت تراكيز الرصاص في معظم العينات أقل من الحد الأعظمي المسموح به بينما أظهرت النتائج وجود عدد من العينات تحتوي على نزر كوبالت متبقية أعلى من الحد الأعظمي المسموح به. بالمقابل تبين أن معظم العينات المدروسة تحتوي على نسب مرتفعة من الكادميوم تجاوزت الحد الأعظمي المسموح به في المواصفات العالمية تبعاً لمنظمة الصحة العالمية WHO (Pb:10, Co:0.4, Cd:0.3 mg/kg). The concentrations of some heavy metals, lead (Pb), cadmium (Cd) and cobalt (Co), in 110 samples of common spices available at local markets in Syria were digested by HNO3, then determined by Atomic Absorption Spectrophotometer AAS. The study has shown that metal concentrations vary according to the edible part (root, stem, leaf and fruit). Heavy metals were present in all samples at different levels. The concentration of heavy metals varied from trace to higher concentration. The maximum levels of lead, cadmium and cobalt in the samples on dry weight basis were 37, 3.2 and 2.4 mg kg-1, respectively. The analytical results obtained for the heavy metals indicate that Lead was present in the majority of samples at concentrations well below the acceptable daily intake recommended by the World Health Organization, while the cobalt was present in some samples at concentrations higher than the acceptable level. The cadmium concentration in the major of samples was too much higher than the acceptable level in WHO (Pb:10, Co:0.4, Cd:0.3 mg/kg) .